PENGARUH KEPUASAN PENGELOLAAN SUMBER DAYA MANUSIA TERHADAP KINERJA DAN LOYALITAS DOSEN DAN TENAGA KEPENDIDIKAN IAIN PADANGSIDIMPUAN - Dra. ASNAH, M.A (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2017)
The problems of this research come from many aspects; one of them is from human resources, it is about managerial system, discipline, responsibility, quality, motivation, and spirit to work. This research is aimed to know the level of satisfaction, performance, and loyalty of the lecturers and educators. It is also to examine the effectiveness of organizing the human resources satisfaction to the performance and loyalty in IAIN Padangsidimpuan. Quantitative research has been done in this research in the type of correlational by giving questionnaires as the instrument which is given to 74 sample of this research. The data have been analysed by using simple regression. Then, the data shown that the range of satisfaction to the human sources management is about 52.70% with mean score of the satisfaction is 52.7973, it is in the level of enough or medium. The range of performance is also in the level enough or medium, it is for 81.08% or in mean score is 78.9865; meanwhile the loyalty is on the high category, it is for 83.78% with the mean score is 76.06135. To test the hypothesis, it is done by using simple regression. The result of the regression from the first hypothesis is 0.291, and hypothesis is accepted. It means that the satisfaction of human resources management has positive effects to the lecturer’s and educators’ performance. Then, the second hypothesis is also accepted, because the coefficient correlation between the satisfaction of human resources management and the lecturers’ and educators’ loyalty is 0.282. Both hypothesis in this research are accepted based on the result of regression